PENGEMBANGAN BAHAN AJAR MATEMATIKA UNTUK PESERTA DIDIK TUNA GRAHITA RINGAN - Leny Hartati; Siti Nur Azizah (Universitas Sultan Ageng Tirtayasa, 2019)
The purpose of this study was to develop appropriate teaching materials and in accordance with mathematics learning for intellectual disabilities students. The development of learning design used refers to the instructional development model (MPI) by Atwi Suparman. The instructional development model includes the definition phase, the development stage, the stage of designing and implementing formative evaluations. The quality of mathematics teaching materials in the form of LKS for intellectual disabilities students based on expert is good. Teaching materials in the form of LKS are expected to facilitate teachers and parents to assist intellectual disabilities students in understanding mathematical material. Keywords: Mathematics Learning Module, Mild Mentally Retarded